The Development of the Character-Based Science Comics Learning Media to Improve Self-Reliance Learning the Students of SMP - Utami Sulistya; Anti Kolonial Projosantoso (Universitas Negeri Yogyakarta, 2019)
The purposes of this research were: 1) to produce, 2) to know the quality, and 3) to know the effect character-based science comic learning media in improving the self-reliance learning of the students on Junior High School and the improvement of the character building. This particular research was Research and Development (R and D) referring to 10 steps developed by Borg and Gall, but this research was conducted only for 1-9 steps. The subjects of the research were 36 students; 10 students participated in the preliminary field test and 26 students in the main field test. Data collection techniques were interviews, questionnaires, and observations. The result of the research showed that: 1) the developed character-based science comic learning media developed using steps proposed by Borg and Gall, 2) the quality of the Science comic learning media is good, and 3) learning using the science comic learning media improve the students’ self-reliance learning and character building.